Negative electrode material, preparation method thereof and lithium ion battery

By introducing carbon materials into the negative electrode materials of lithium-ion batteries and optimizing the distribution of lithium silicates, the problems of poor circulation performance and low first-time efficiency of the negative electrode materials of lithium-ion batteries are solved, and more stable storage and longer cycle life are achieved.

CN119695129APending Publication Date: 2025-03-25BTR NEW MATERIAL GRP CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311231152.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode materials have expansion problems during the circulation process, resulting in a decrease in circulation performance, and the first-time efficiency of pre-lithium silicon oxygen materials is low, which poses poor processing performance and safety risks.

Method used

The negative electrode material including silicon-based active substances and carbon materials located on the surface of silicon-based active substances is adopted. The component ratio is optimized by XRD ray diffraction method, and surface modification and prelithiation treatment are used to improve the uniform distribution of lithium silicate and carbon coating, and enhance the structural stability of the electrode sheet.

Benefits of technology

It improves the storage stability of the negative electrode material, extends the cycle life, improves the structural stability and circulation performance of the electrode sheet, reduces the destructive effect of lithium silicate on the binder, and improves the first-time efficiency of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695129A_ABST
    Figure CN119695129A_ABST
Patent Text Reader

Abstract

The invention relates to a negative electrode material, a preparation method thereof and a lithium ion battery, the negative electrode material comprises a silicon-based active substance and a carbon material located on at least part of the surface of the silicon-based active substance, and the silicon-based active substance comprises a silicon simple substance and lithium silicate; according to the negative electrode material disclosed by the invention, the storage stability of negative electrode slurry can be improved, the cycle life of the negative electrode material can be prolonged, the bonding capacity of the negative electrode material and a current collector can be improved, and the high-temperature storage performance of a battery cell can be improved by controlling the variety and crystallization degree of lithium silicate in the material, so that the cycle performance of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials, and in particular to negative electrode materials and preparation methods thereof, and lithium ion batteries. Background Art

[0002] Lithium-ion batteries have been widely used in portable electronic products and electric vehicles due to their advantages such as high operating voltage, long cycle life, no memory effect, low self-discharge, and environmental friendliness. At present, commercial lithium-ion batteries mainly use graphite-based negative electrode materials, but their theoretical specific capacity is only 372mAh / g, which cannot meet the future demand for high energy density of lithium-ion batteries. Although the existing Si has a theoretical capacity of up to 4200mAh / g, its expansion is up to 300%, which affects the cycle performance and restricts market promotion and application. The corresponding silicon-oxygen material has better cycle performance, but the first efficiency is low. During the first charge, 20-50% of the lithium is consumed for SEI film formation, which greatly reduces the first coulomb efficiency. As the first efficiency of the positive electrode material becomes higher and higher, it is particularly important to improve the first efficiency of silicon-oxygen materials.

[0003] At present, the most effective way to improve the initial effect of silicon oxide materials is to pre-dope them with lithium so that the irreversible lithium consumption phase in the silicon oxide materials can be reacted in advance. The existing industrial method is to directly coat the surface of the electrode with a lithium layer to reduce the consumption of positive electrode lithium. However, this method has high requirements for the operating environment and has great safety risks, so it is difficult to achieve industrial promotion.

[0004] Under the current state of technological development, there is a general problem of poor processing performance in the process of obtaining first-effect improvement by pre-lithiation on the silicon oxide material side, which is mainly manifested in the following aspects: the slurry prepared with pre-lithiation silicon oxide negative electrode material has a short stable storage time, and is prone to sedimentation, stratification, and gas production during storage, resulting in uneven distribution of active substances in the coated pole pieces, large differences in pole piece thickness and surface density, and uneven appearance of the pole pieces, making it impossible to assemble the full battery; the pre-lithiation uniformity of pre-lithiation silicon oxide is difficult to control, resulting in uneven types and contents of lithium silicates in the material, and the prepared slurry is unstable, which can easily lead to uneven coated pole pieces, further reducing the peel strength of the pole pieces, and the active substances are easily peeled off from the current collector; due to the introduction of lithium sources and the generation of lithium silicates, the pre-lithiation silicon oxide material will break the original stable structure of the silicon oxide material and shorten the cycle life of the material. Summary of the invention

[0005] In view of the above-mentioned problems existing in the prior art, the purpose of the present application is to provide a negative electrode material and a preparation method thereof, a negative electrode slurry, and a lithium-ion battery. The negative electrode material provided in the present application can improve the storage stability of the negative electrode slurry, extend the cycle life of the negative electrode material, increase the bonding ability between the negative electrode material and the current collector, and improve the high-temperature storage performance of the battery cell, thereby improving the cycle performance of the lithium-ion battery.

[0006] In a first aspect, the present application provides a negative electrode material, the negative electrode material comprising a silicon-based active material and a carbon material located on at least a portion of the surface of the silicon-based active material, the silicon-based active material comprising silicon and lithium silicate;

[0007] Determined by XRD ray diffraction method, in the X-ray diffraction spectrum of the negative electrode material, the peak intensity of the strongest diffraction peak of the negative electrode material in the range of 2θ of 18° to 20° is A1, the peak intensity of the strongest diffraction peak in the range of 2θ of 26° to 27.9° is A2, and the peak intensity of the strongest diffraction peak at 2θ of 32° to 34° is A3, and A1+A2+A3=A;

[0008] The peak intensity of the strongest diffraction peak of the negative electrode material in the range of 2θ of 16° to 17° is B1, the peak intensity of the strongest diffraction peak in the range of 2θ of 22° to 25.9° is B2, and the peak intensity of the strongest diffraction peak in the range of 2θ of 36° to 38° is B3, B1+B2+B3=B;

[0009] The peak intensity of the strongest diffraction peak of the negative electrode material in the range of 28° to 30° at 2θ is C1, the peak intensity of the strongest diffraction peak in the range of 46° to 48° at 2θ is C2, and the peak intensity of the strongest diffraction peak in the range of 56° to 58° at 2θ is C3, C1+C2+C3=C;

[0010] And the relationship between A, B, and C satisfies: 0<(A+B) / C≤10, 0<(A+C) / B≤5.

[0011] In some embodiments, the negative electrode material is tested using a powder resistivity tester, and the powder conductivity of the negative electrode material at a powder density of ρ1 is measured to be σ1, and the powder conductivity of the negative electrode material at a powder density of ρ2 is measured to be σ2, and the following relationship is satisfied: (σ2-σ1) / (ρ2-ρ1)≤0.8.

[0012] In some embodiments, the silicon-based active material further includes a silicon-oxygen composite.

[0013] In some embodiments, the molar ratio of oxygen atoms to silicon atoms in the negative electrode material is 0.5-2.

[0014] In some embodiments, the silicon single substance includes nano-silicon grains, and the particle size of the nano-silicon grains is 0 nm to 20 nm, and 0 nm is not included.

[0015] In some embodiments, the carbon material includes at least one of amorphous carbon, graphene, graphite, carbon nanotubes, and carbon fibers.

[0016] In some embodiments, the lithium silicate includes at least one of Li2SiO3, Li2Si2O5, and Li4SiO4.

[0017] In some embodiments, the mass content of the carbon material in the negative electrode material is less than or equal to 10%.

[0018] In some embodiments, the specific surface area of ​​the negative electrode material is less than or equal to 10 m 2 / g.

[0019] In some implementations, the relationship between A, B, and C also satisfies: 1≤(B+C) / A≤30.

[0020] In some embodiments, the mass content of silicon in the negative electrode material is 20% to 70%.

[0021] In some embodiments, the mass content of silicate in the negative electrode material is 30% to 75%.

[0022] In some embodiments, the pH value of the negative electrode material is 7.2-11.0.

[0023] In some embodiments, the active material, carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber are mixed in a mass ratio of 95.3:1.3:1.5:1.9 to form a negative electrode slurry with a solid content of 50%, wherein the active material includes the negative electrode material and graphite in a mass ratio of 9:1; the rheological properties of the negative electrode slurry are tested using a German Haake rotational rheometer to obtain a rheological curve of the negative electrode slurry; in the rheological curve, when the shear rate is 0S -1 、150S -1 、300S -1 When , the corresponding shear stresses in the rheological curve are τ0, τ1, τ2, and the relationship between the shear stresses satisfies: 2τ1>(τ2-τ0).

[0024] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising the following steps:

[0025] Silicon oxide SiO x Place in an acid solution for the first surface modification treatment, wherein 0<x<2;

[0026] The silicon oxide SiO x The mixture with the reducing lithium-containing compound is subjected to a pre-lithiation treatment and a carbon coating treatment at 300° C. to 800° C. to obtain a precursor, wherein 0<x<2;

[0027] The precursor is subjected to a second surface modification treatment to obtain a negative electrode material, wherein the negative electrode material includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, and the silicon-based active substance includes silicon and lithium silicate.

[0028] In some embodiments, the acid solution includes at least one of hydrofluoric acid, nitric acid, fluorosulfonic acid, fluoroantimonysulfonic acid, hydrochloric acid, hydrobromic acid, and hydroiodic acid.

[0029] In some embodiments, the concentration of the acid solution is ≤2 mol / L.

[0030] In some embodiments, the temperature of the first surface modification treatment is 30°C to 100°C.

[0031] In some embodiments, the first surface modification treatment is performed for 2 hours to 8 hours.

[0032] In some embodiments, the preparation method further comprises treating the silicon oxide SiO x Carry out solid-liquid separation, washing and drying.

[0033] In some embodiments, the preparation method further comprises treating the silicon oxide SiO x Solid-liquid separation, washing and drying are performed, and the drying temperature is 50°C to 180°C.

[0034] In some embodiments, the silicon oxide is silicon monoxide.

[0035] In some embodiments, the reducing lithium-containing compound includes at least one of lithium hydride, alkyl lithium, metallic lithium, lithium aluminum hydride, lithium amide, lithium borohydride, and lithium silicon alloy.

[0036] In some embodiments, the mass ratio of the silicon oxide after the first surface modification treatment to the reducing lithium-containing compound is 1:(0.03-0.2).

[0037] In some embodiments, the pre-lithiation treatment is performed in a protective atmosphere.

[0038] In some embodiments, the protective atmosphere includes at least one of nitrogen, helium, neon, argon, krypton, and xenon.

[0039] In some embodiments, the pre-lithiation treatment lasts for 3 hours to 9 hours.

[0040] In some embodiments, the carbon coating process includes at least one of a liquid phase coating method, a gas phase coating method, and a solid phase coating method.

[0041] In some embodiments, the carbon-coated coating material includes at least one of amorphous carbon, graphene, graphite, carbon nanotubes, and carbon fibers.

[0042] In some embodiments, the lithium silicate includes at least one of Li2SiO3, Li2Si2O5, and Li4SiO4.

[0043] In some embodiments, the method comprises: treating the silicon oxide SiO x Before the mixture with the reducing lithium-containing compound is subjected to a pre-lithiation treatment at 300°C to 800°C, the silicon oxide SiO x The mixture is mixed with a reducing lithium-containing compound.

[0044] In some embodiments, the mixing process is carried out at a temperature of 60°C to 320°C.

[0045] In some embodiments, the mixing treatment time is 0.5 h to 10 h.

[0046] In some embodiments, the equipment required for the mixing process includes at least one of an equipment with a dispersing function and an equipment with a shearing force effect.

[0047] In some embodiments, the second surface treatment includes at least one of purification treatment, coating treatment, heat treatment, oxidation treatment, and etching treatment.

[0048] In some embodiments, the temperature of the second surface treatment is 50°C to 900°C.

[0049] In some embodiments, the second surface treatment lasts for 0.5 h to 10 h.

[0050] In some embodiments, the second surface treatment comprises placing the precursor in an aluminum hydroxide solution for purification.

[0051] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode material described in the first aspect or the negative electrode material prepared by the preparation method described in the second aspect.

[0052] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:

[0053] The negative electrode material provided in the present application includes a silicon-based active substance, and the silicon-based active substance includes silicon and lithium silicate. By XRD diffraction method, in the X-ray diffraction spectrum of the negative electrode material, A represents Li2SiO3, B represents Li2Si2O5, and C represents silicon. When the relationship between A, B, and C satisfies: 0<(A+B) / C≤10, 0<(A+C) / B≤5, the three components of Li2SiO3, Li2Si2O5 and silicon in the negative electrode material influence each other and reach a balance. The lithiation uniformity of the negative electrode material is good, and the processing performance of the negative electrode material is relatively stable. The negative electrode material can be evenly dispersed and suspended in the binder glue, so that the prepared slurry can be stably stored; in addition, the destructive effect of lithium silicate on the binder can be reduced, the structural stability of the electrode sheet is improved, and the cycle life of the material is extended. The negative electrode material provided in the present application can reduce the destructive effect of alkalinity on the binder by regulating the type and degree of crystallization of lithium silicate, improve the structural stability of the electrode, improve the cycle performance of the material, and extend the cycle life.

[0054] The negative electrode material preparation method provided in the present application is to prepare silicon oxide SiO x The first surface modification treatment is carried out in an acid solution. The acid solution is effective for the silicon oxide SiO x The surface is oxidized and etched to form weak defect sites, which can increase the reaction sites of the pre-lithiation process, promote a more uniform pre-lithiation reaction, obtain more lithium silicate growth sites, and facilitate the uniform distribution of lithium silicate inside the particles, which helps to adjust the crystal phase type and content of lithium silicate. In addition, the silicon oxide SiO x Pre-lithiation treatment can greatly reduce the catalytic growth of silicon grains by lithium silicate; due to the first surface modification of silicon oxide SiO x The surface has uniformly distributed growth sites, which will contain silicon oxide SiO after the first surface modification treatment. x Pre-lithiation treatment with a mixture of reducing lithium-containing compounds can improve the utilization rate of lithium and the uniformity of the distribution of pre-lithiation products. The uniform distribution of pre-lithiation products is beneficial to buffer the volume change of silicon materials during charging and discharging, stabilize the overall structure of the negative electrode material, extend the cycle life, reduce the regeneration of SEI film, and enhance the pre-lithiation effect and the initial effect of the material. By performing a second surface modification treatment on the precursor and adjusting the surface morphology of the negative electrode material, on the one hand, the interface can be stabilized to form a SEI film with more stable stage performance, reduce the risk of corrosion of the negative electrode material in the electrolyte, and improve the high-temperature storage performance of the battery cell. On the other hand, the adhesion strength of the binder to the negative electrode material can be improved, the peeling strength of the electrode sheet can be enhanced, the rebound of the electrode sheet can be reduced, and the conductive network of the electrode sheet can be stabilized, thereby improving the cycle life of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0056] Figure 1 A process flow chart of the preparation method of the negative electrode material provided in this application;

[0057] Figure 2 This is a relationship diagram between the powder density and powder conductivity of the negative electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0058] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0059] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0061] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0062] In a first aspect, the present application provides a negative electrode material, the negative electrode material comprising a silicon-based active material and a carbon material located on at least a portion of the surface of the silicon-based active material, the silicon-based active material comprising silicon and lithium silicate;

[0063] The XRD ray diffraction method is used to measure that in the X-ray diffraction spectrum of the negative electrode material, the peak intensity of the strongest diffraction peak of the negative electrode material in the range of 2θ of 18° to 20° is A1, the peak intensity of the strongest diffraction peak in the range of 2θ of 26° to 27.9° is A2, and the peak intensity of the strongest diffraction peak at 2θ of 32° to 34° is A3, and A1+A2+A3=A;

[0064] The peak intensity of the strongest diffraction peak of the negative electrode material in the range of 2θ of 16° to 17° is B1, the peak intensity of the strongest diffraction peak in the range of 2θ of 22° to 25.9° is B2, and the peak intensity of the strongest diffraction peak in the range of 2θ of 36° to 38° is B3, B1+B2+B3=B;

[0065] The peak intensity of the strongest diffraction peak of the negative electrode material in the range of 28° to 30° at 2θ is C1, the peak intensity of the strongest diffraction peak in the range of 46° to 48° at 2θ is C2, and the peak intensity of the strongest diffraction peak in the range of 56° to 58° at 2θ is C3, C1+C2+C3=C;

[0066] And the relationship between A, B, and C satisfies: 0<(A+B) / C≤10, 0<(A+C) / B≤5.

[0067] The negative electrode material provided by the present application includes a silicon-based active material, and the silicon-based active material includes silicon and lithium silicate. The XRD ray diffraction method is used to measure that in the X-ray diffraction spectrum of the negative electrode material, A represents Li2SiO3, B represents Li2Si2O5, and C represents silicon. When the relationship between A, B, and C satisfies: 0<(A+B) / C≤10, 0<(A+C) / B≤5, the three components of Li2SiO3, Li2Si2O5, and silicon in the negative electrode material affect each other and reach a balance. The lithiation uniformity of the negative electrode material is good, and the processing performance of the negative electrode material is relatively stable. The negative electrode material can be evenly dispersed and suspended in the binder glue, so that the prepared slurry can be stably stored; in addition, the destructive effect of lithium silicate on the binder can be reduced, the structural stability of the pole piece can be improved, and the cycle life of the material can be extended. The negative electrode material provided by the present application can reduce the destructive effect of alkalinity on the binder by regulating the type and crystallization degree of lithium silicate, improve the structural stability of the pole piece, improve the cycle performance of the material, and extend the cycle life.

[0068] Specifically, the value of (A+B) / C may be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, etc., which is not limited here. The value of (A+C) / B may be, for example, 1, 2, 3, 4 or 5, etc., which is not limited here.

[0069] In some implementations, the relationship between A, B, and C also satisfies: 1≤(B+C) / A≤30. Specifically,

[0070] The value of (B+C) / A can be, for example, 1, 3, 5, 8, 10, 12, 15, 17, 20, 21, 23, 25, 28 or 30, etc., and is not limited here.

[0071] It can be understood that there are three components distributed in the negative electrode material, namely A representing Li2SiO3, B representing Li2Si2O5 and C representing silicon; when the value of (B+C) / A is greater than 30, or the value of (A+B) / C is greater than 10, or the value of (A+C) / B is greater than 5, it means that the relative relationship between the three components of Li2SiO3, Li2Si2O5 and silicon in the negative electrode material is unbalanced, which will reduce the storage performance of the negative electrode slurry made of the negative electrode material, and will further hinder the use of the negative electrode material. The negative electrode slurry is prone to sedimentation, stratification and gas production during storage, resulting in uneven distribution of active substances in the coated electrode, large differences in electrode thickness and surface density, and uneven appearance of the electrode, so that the full battery cannot be assembled.

[0072] In some embodiments, the negative electrode material is tested using a powder resistivity tester, and the powder conductivity of the negative electrode material at a powder density ρ1 is measured to be σ1, and the powder conductivity of the negative electrode material at a powder density ρ2 is measured to be σ2, and the following relationship is satisfied: (σ2-σ1) / (ρ2-ρ1)≤0.8. Specifically, the value of (σ2-σ1) / (ρ2-ρ1) can be 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0073] It can be understood that the powder conductivity of the negative electrode material is related to the apparent morphology and internal structure of the material, and can reflect the electronic conductivity of the material. The silicon oxide material after pre-lithiation treatment may reduce the overall electronic conductivity of the material due to the increase of lithium silicate. The powder conductivity of the negative electrode material changes with the change of powder density. The present application controls the balance between the three components of Li2SiO3, Li2Si2O5 and silicon element, and then balances the relationship between powder conductivity and powder density, ensures electrical contact between particles, improves the stability of the conductive network between particles, increases the probability of electrical contact between particles during the cycle, and extends the cycle life of the material. In some embodiments, the molar ratio of oxygen atoms to silicon atoms in the negative electrode material is 0.5 to 2, specifically 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2, etc., of course, it can also be other values ​​within the above range, which are not limited here. In some embodiments, the silicon-based active material further comprises a silicon-oxygen composite, wherein the silicon-oxygen composite comprises oxygen atoms and silicon atoms, and the molar ratio of oxygen atoms to silicon atoms is 0.5 to 2. The silicon-oxygen composite can be represented by the general formula SiO x(0.5≤x≤2). It can be a material formed by silicon particles dispersed in SiO2, or a material having a tetrahedral structural unit, in which the silicon atom is located at the center of the tetrahedral structural unit, and the silicon atom and the oxygen atom are located at the four vertices of the tetrahedral structural unit.

[0074] In some embodiments, the silicon element includes nano-silicon grains, and the particle size of the nano-silicon grains is 0nm to 20nm, and 0nm is not included. Specifically, the particle size of the nano-silicon grains can be 1nm, 3nm, 5nm, 8nm, 10nm, 12nm, 15nm or 20nm, etc., which is not limited here. It can be understood that under the same silicon content, compared with large-sized crystalline silicon grains, due to the isotropic expansion of silicon, the expansion stress of small-sized silicon grains is more uniform, the silicon grain expansion effect is smaller, and the cycle life is longer, which can be beneficial to improve the cycle performance and rate performance of the negative electrode material.

[0075] In some embodiments, the carbon material includes at least one of amorphous carbon, graphene, graphite, carbon nanotubes, and carbon fibers.

[0076] In some embodiments, the lithium silicate includes at least one of Li2SiO3, Li2Si2O5, and Li4SiO4.

[0077] In some embodiments, the mass content of carbon material in the negative electrode material is less than or equal to 10%, specifically 0.1%, 1%, 2%, 3%, 5%, 7%, 8%, 9% or 10%, and of course other values ​​within the above range are also possible, which are not limited here.

[0078] In some embodiments, the specific surface area of ​​the negative electrode material is less than or equal to 10 m 2 / g, specifically 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g or 10m 2 / g, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0079] In some embodiments, the mass content of silicon in the negative electrode material is 20% to 70%, specifically 20%, 24%, 28%, 30%, 35%, 40%, 48%, 52%, 56%, 60%, 63%, 65%, 67% or 70%, etc., which is not limited here.

[0080] In some embodiments, the mass content of silicate in the negative electrode material is 30% to 75%, specifically 30%, 32%, 35%, 38%, 40%, 45%, 50%, 56%, 60%, 64%, 67%, 70%, 72%, 73% or 75%, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0081] In some embodiments, the pH value of the negative electrode material is 7.2 to 11.0. The pH value of the negative electrode material can be 7.2, 7.6, 7.8, 8, 8.3, 8.5, 8.7, 9.6, 9.9, 10, 10.25, 10.36, 10.47, 10.58, 10.87, 10.98 or 11, etc., which are not limited here.

[0082] In some embodiments, the active material, carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber are mixed in a mass ratio of 95.3:1.3:1.5:1.9 to form a negative electrode slurry with a solid content of 50%, wherein the active material includes a negative electrode material and graphite in a mass ratio of 9:1; the rheological properties of the negative electrode slurry are tested using a German Haake rotational rheometer to obtain a rheological curve of the negative electrode slurry; in the rheological curve, when the shear rate is 0S -1 、150S -1 、300S -1 When , the corresponding shear stresses in the rheological curve are τ0, τ1, τ2, and the relationship between the shear stresses satisfies: 2τ1>(τ2-τ0).

[0083] It can be understood that the relationship between the shear stress in the rheological curve of the above-mentioned negative electrode slurry is related to the leveling performance, sagging performance and sedimentation performance of the negative electrode material. By limiting this relationship, the processing performance of the negative electrode material can be improved and the storage stability of the negative electrode material can be improved. By limiting the shear rate-shear stress, the fluidity and stability of the negative electrode slurry can be improved, the uniformity and consistency of the pole piece can be increased, the bonding strength between the active material and the current collector can be increased, and the active material can be prevented from falling off from the current collector. When the rheological curve satisfies the above formula, the material has good anti-settling performance, anti-sagging performance and storage stability. In addition, the active material on the pole piece can be evenly attached to the current collector, which is beneficial to improve the peel strength of the pole piece. When 2τ1≤(τ2-τ0), the negative electrode material is prone to sedimentation, tailing, and stratification, which is not conducive to pole piece coating, and also reduces the consistency of the battery.

[0084] In a second aspect, the present application provides a method for preparing a negative electrode material, such as Figure 1 As shown, the following steps are included:

[0085] S100, silicon oxide SiO x Place in an acid solution for the first surface modification treatment, wherein 0<x<2;

[0086] S200, comprising silicon oxide SiO after the first surface modification treatment x The mixture with the reducing lithium-containing compound is subjected to a pre-lithiation treatment and a carbon coating treatment at 300° C. to 800° C. to obtain a precursor, wherein 0<x<2;

[0087] S300, subjecting the precursor to a second surface modification treatment to obtain a negative electrode material, wherein the negative electrode material includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, and the silicon-based active substance includes silicon and lithium silicate.

[0088] The negative electrode material preparation method provided in the present application is to prepare silicon oxide SiO x The first surface modification treatment is carried out in an acid solution. The acid solution is effective for the silicon oxide SiO x The surface is oxidized and etched to form weak defect sites, which can increase the reaction sites of the pre-lithiation process, promote a more uniform pre-lithiation reaction, obtain more lithium silicate growth sites, and facilitate the uniform distribution of lithium silicate inside the particles, which helps to adjust the crystal phase type and content of lithium silicate. In addition, the silicon oxide SiO x Pre-lithiation treatment can greatly reduce the catalytic growth of silicon grains by lithium silicate; due to the first surface modification of silicon oxide SiO x The surface has uniformly distributed growth sites, which will contain silicon oxide SiO after the first surface modification treatment. x Pre-lithiation treatment with a mixture of reducing lithium-containing compounds can improve the utilization rate of lithium and the uniformity of the distribution of pre-lithiation products. The uniform distribution of pre-lithiation products is beneficial to buffer the volume change of silicon materials during charging and discharging, stabilize the overall structure of the negative electrode material, extend the cycle life, reduce the regeneration of SEI film, and enhance the pre-lithiation effect and the initial effect of the material. By performing a second surface modification treatment on the precursor and adjusting the surface morphology of the negative electrode material, on the one hand, the interface can be stabilized to form a SEI film with more stable stage performance, reduce the risk of corrosion of the negative electrode material in the electrolyte, and improve the high-temperature storage performance of the battery cell. On the other hand, the adhesion strength of the binder to the negative electrode material can be improved, the peeling strength of the electrode piece can be enhanced, the rebound of the electrode piece can be reduced, and the conductive network of the electrode piece can be stabilized, thereby improving the cycle life of the negative electrode material.

[0089] The following is a detailed description of the preparation method provided in this scheme:

[0090] Step S100, silicon oxide SiO x The first surface modification treatment is carried out in an acid solution, wherein 0<x<2.

[0091] In some embodiments, the silicon oxide is SiOx , where 0<x<2, SiO x Specifically, it can be SiO 0.5 、SiO 0.7 、SiO、SiO 1.2 、SiO 1.4 、SiO 1.6 、SiO 1.8 or SiO 1.9 It should be noted that SiO x The composition of lithium ions is relatively complex, and it can be understood that at least one of amorphous silicon and crystalline silicon is uniformly dispersed in SiO2. At high temperatures, its thermodynamic properties are very unstable and it is easy to undergo a reduction reaction with a lithium source to form lithium silicate.

[0092] In some embodiments, the acid solution includes at least one of hydrofluoric acid, nitric acid, fluorosulfonic acid, fluoroantimonysulfonic acid, hydrochloric acid, hydrobromic acid, and hydroiodic acid. It is understood that the acid solution is used to treat silicon oxide SiO x Surface modification treatment is performed to achieve silicon oxide SiO x Surface oxidation and etching can be done on silicon oxide SiO x The formation of slight defects on the surface increases the reaction sites of the pre-lithiation process, promotes a more uniform pre-lithiation reaction, obtains more lithium silicate growth sites, and is conducive to the uniform distribution of lithium silicate inside the particles. When the amount of pre-lithiation is fixed, it helps to adjust the crystal phase type and content of lithium silicate. In addition, the use of surface-modified silicon oxide for pre-lithiation treatment can greatly reduce the catalytic growth of lithium silicate on silicon grains.

[0093] In some embodiments, the concentration of the acid solution is ≤ 2 mol / L. Specifically, the concentration of the acid solution can be 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L or 2 mol / L, etc., which is not limited here.

[0094] In some embodiments, the temperature of the first surface modification treatment is 30°C to 100°C, specifically 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0095] In some embodiments, the time for the first surface modification treatment is 2 h to 8 h, specifically 2 h, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0096] In some embodiments, the preparation method further comprises treating the silicon oxide SiO x Carry out solid-liquid separation, washing and drying.

[0097] In some embodiments, the preparation method further comprises treating the silicon oxide SiO x Solid-liquid separation, washing and drying are performed, and the drying temperature is 50° C. to 180° C. Specifically, the drying temperature can be 50° C., 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., 160° C., 170° C. or 180° C., which is not limited here.

[0098] Step S200, the silicon oxide SiO x The mixture with the reducing lithium-containing compound is subjected to a pre-lithiation treatment and a carbon coating treatment at 300° C. to 800° C. to obtain a precursor, wherein 0<x<2.

[0099] In the above scheme, the temperature of the pre-lithiation treatment can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 710°C or 800°C, etc., and of course it can also be other values ​​within the above range, which are not limited here. It can be understood that when the temperature of the pre-lithiation treatment is too low, the reducing lithium-containing compound cannot react completely with the silicon oxide, and the remaining silicon oxide will cause the oxygen content in the negative electrode material to be high, which is not conducive to the improvement of the first efficiency of the material; when the temperature of the pre-lithiation treatment is too high, the reducing lithium-containing compound and the silicon oxide react violently, and the speed and amount of lithium silicate generated are fast and large. On the one hand, it will catalyze the growth of silicon grains in the material, causing the cycle performance of the negative electrode material to deteriorate; on the other hand, it will reduce the stability of the slurry, making the slurry unable to be stably stored. Controlling the pre-lithiation temperature within this range is beneficial to the reaction between the lithium source and silicon oxide, to balancing the crystal phase type and content of lithium silicate, and to obtaining silicon grains of appropriate size, thereby further improving the slurry storage stability of the material.

[0100] In some embodiments, the silicon oxide is silicon monoxide. It is understandable that when silicon monoxide is used as the silicon oxide, the problem of unstable processing performance after the silicon monoxide is doped with lithium to improve the initial effect can be effectively solved.

[0101] In some embodiments, the reducing lithium-containing compound includes at least one of lithium hydride, alkyl lithium, metallic lithium, lithium aluminum hydride, lithium amide, lithium borohydride, and lithium silicon alloy. It can be understood that the reducing lithium-containing compound is selected as the lithium source for the pre-lithiation treatment. Since the silicon oxide surface after the first surface modification has uniformly distributed growth sites, the mixture containing the silicon oxide after the first surface modification treatment and the reducing lithium-containing compound is subjected to pre-lithiation treatment, which can improve the utilization rate of lithium and the uniformity of the distribution of the pre-lithiation product; improving the utilization rate of lithium is conducive to reducing costs and improving the pre-lithiation effect (first effect); the pre-lithiation product is evenly distributed, which is conducive to buffering the volume change of the silicon material during the charge and discharge process, stabilizing the overall structure of the material, extending the cycle life of the material, and reducing the regeneration of the SEI film.

[0102] In some embodiments, the mass ratio of silicon oxide to the reducing lithium-containing compound after the first surface modification treatment is 1:(0.03-0.2), specifically 1:0.03, 1:0.05, 1:0.08, 1:0.1, 1:0.15 or 1:0.2, etc., which is not limited here.

[0103] In some embodiments, the pre-lithiation treatment is performed in a protective atmosphere. It can be understood that the pre-lithiation treatment in a protective atmosphere can reduce the risk of introducing oxygen elements, ensure the initial effect of the pre-lithiation material is improved, and also help to regulate the composition of lithium silicate, further improving the storage stability of the slurry.

[0104] In some embodiments, the protective atmosphere includes at least one of nitrogen, helium, neon, argon, krypton, and xenon.

[0105] In some embodiments, the pre-lithiation treatment time is 3 hours to 9 hours, specifically 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours or 9 hours, etc., and of course, other values ​​within the above range are also possible, which are not limited here. It can be understood that the pre-lithiation treatment time is within the above range, and the Li2SiO3 can be fully calcined and fully converted into Li2Si2O5.

[0106] In some embodiments, the carbon coating process includes at least one of a liquid phase coating method, a gas phase coating method, and a solid phase coating method.

[0107] In some embodiments, the carbon-coated coating material includes at least one of amorphous carbon, graphene, graphite, carbon nanotubes and carbon fibers. Preferably, the carbon-coated coating material is amorphous carbon. It can be understood that amorphous carbon is produced by high-temperature pyrolysis and has a certain degree of graphitization. Using amorphous carbon to coat the surface of silicon oxide can improve the conductivity of the negative electrode material on the one hand, and on the other hand, the amorphous carbon produced by high-temperature pyrolysis has a relatively developed void structure. Coating it on the surface of silicon oxide can inhibit the volume expansion of the negative electrode material, which is beneficial to improving the cycle performance of the negative electrode material.

[0108] In some embodiments, the lithium silicate includes at least one of Li2SiO3, Li2Si2O5, and Li4SiO4.

[0109] In some embodiments, the method further includes mixing the mixture of silicon oxide after the first surface modification treatment and the reducing lithium-containing compound before pre-lithiation treatment of the mixture at 300°C to 800°C.

[0110] In some embodiments, the temperature of the mixing treatment is 60°C to 320°C, specifically 60°C, 70°C, 80°C, 90°C, 100°C, 150°C, 200°C, 250°C, 300°C, 310°C or 320°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0111] In some embodiments, the mixing treatment time is 0.5h to 10h, specifically 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0112] In some embodiments, the equipment required for the mixing process includes at least one of an equipment with a dispersing function or an equipment with a shearing force. It can be understood that the use of an equipment with a high-speed dispersing function and a shearing force to mix the mixture containing the silicon oxide after the first surface modification treatment and the reducing lithium-containing compound before pre-lithiation can effectively alleviate the severity of the reaction in the early stage of pre-lithiation, help to regulate the lithium silicate component to meet the requirements of the present invention, thereby improving the storage stability of the slurry and the bonding ability of the active material in the pole piece.

[0113] In some embodiments, before subjecting the mixture comprising the silicon oxide after the first surface modification treatment and the reducing lithium-containing compound to a pre-lithiation treatment, the method further comprises subjecting the silicon oxide after the first surface modification treatment to a carbon coating treatment.

[0114] It can be understood that the carbon coating treatment can be carried out before the mixture of silicon oxide after the first surface modification treatment and the reducing lithium-containing compound is pre-lithiated, or it can be carried out after the mixture of silicon oxide after the first surface modification treatment and the reducing lithium-containing compound is pre-lithiated, and there is no limitation here.

[0115] It should be noted that when the carbon coating treatment is carried out before the mixture of silicon oxide after the first surface modification treatment and the reducing lithium-containing compound is pre-lithiated, the carbon coating treatment needs to be carried out before the mixture of silicon oxide after the first surface modification treatment and the reducing lithium-containing compound is mixed.

[0116] Step S300, subjecting the precursor to a second surface modification treatment to obtain a negative electrode material, wherein the negative electrode material comprises a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, and the silicon-based active substance comprises silicon and lithium silicate.

[0117] In some embodiments, the second surface modification treatment includes at least one of purification treatment, coating treatment, heat treatment, oxidation treatment, and etching treatment.

[0118] In some embodiments, the coating treatment may specifically be a secondary carbon coating treatment, a polymer coating treatment, or an inorganic coating treatment, etc., which is not limited herein.

[0119] In a specific implementation, the heat treatment is combined with other methods, such as polymer coating treatment and etching treatment, which are not limited here.

[0120] In some embodiments, the temperature of the second surface modification treatment is 50°C to 900°C, specifically 50°C, 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C or 900°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0121] In some embodiments, the time for the second surface modification treatment is 0.5h to 10h, specifically 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0122] In some embodiments, the second surface modification treatment includes placing the precursor in an aluminum hydroxide solution for purification. It can be understood that since the coatings on the aluminum foil and the separator in the battery system are of the same source, placing the precursor in an aluminum hydroxide solution for purification can make the composed battery system more compatible.

[0123] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode material of the first aspect or the negative electrode material prepared by the preparation method of the second aspect.

[0124] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

[0125] Example

[0126] Example 1

[0127] (1) Silicon monoxide (SiO) is placed in a mixed acid solution of nitric acid and hydrochloric acid with a concentration of 1 mol / L, stirred and dispersed at 50° C. for 4 h, then filtered and washed with pure water, and the obtained product is dried at 80° C. to obtain silicon monoxide (SiO) after surface modification.

[0128] (2) A mixture of 1000 g of surface-modified silicon monoxide (SiO) and 200 g of lithium hydride is placed in a high-speed disperser, argon gas is introduced, the temperature is raised to 80° C., and the mixture is dispersed at 2000 rpm for 1 h for mixing. The mixture is cooled to room temperature and then loaded into a crucible. The crucible is placed in a box furnace for pre-lithiation treatment at 500° C. for 4 h, and the temperature is lowered to 25° C. to obtain a silicon-based active substance. Then, 2% wt of amorphous carbon is coated on the surface of the silicon-based active substance by a liquid phase coating method to obtain a precursor.

[0129] (3) The precursor is placed in Al(OH)3 and purified at 40°C for 2h. The residual alkali solution on the surface of the precursor is removed by filtration and washing. Then, 2%wt of amorphous carbon is coated on the surface of the precursor by a liquid phase coating method to obtain a negative electrode material.

[0130] The negative electrode material prepared in this embodiment includes a silicon-based active material and a carbon material located on at least a portion of the surface of the silicon-based active material, the silicon-based active material includes silicon and lithium silicate, and the silicon includes nano-silicon grains; the negative electrode material is measured by XRD ray diffraction method, and the relationship between A, B, and C in the negative electrode material is calculated through the X-ray diffraction spectrum of the negative electrode material to satisfy: (A+B) / C=4.6, (A+C) / B=2.1, (B+C) / A=12.3, Figure 2 The relationship between the powder density and the powder conductivity of the negative electrode material prepared in this embodiment is shown in FIG. Figure 2 It can be concluded that the relationship between ρ1, ρ2, σ1, and σ2 satisfies: (σ2-σ1) / (ρ2-ρ1)=0.32, and the relationship between the shear forces in the rheological curves satisfies 2τ1>(τ2-τ0).

[0131] The negative electrode material prepared in this embodiment can be stably stored for more than 72 hours after being prepared into negative electrode slurry.

[0132] Example 2

[0133] The negative electrode material was prepared in a method substantially the same as that in Example 1, except that:

[0134] (2) 2% wt of amorphous carbon was coated on the surface of 1000 g of surface-modified silicon monoxide (SiO) by a liquid phase coating method, and then 200 g of lithium hydride was weighed and placed in a high-speed disperser. Argon was introduced, the temperature was raised to 80° C., and the mixture was dispersed at 2000 rpm for 1 h for mixing. The mixture was cooled to room temperature and then loaded into a crucible. The crucible was placed in a box furnace for pre-lithiation treatment at 500° C. for 4 h, and then the temperature was lowered to 25° C. to obtain a precursor.

[0135] The remaining operations are the same as those in Example 1.

[0136] The negative electrode material prepared in this embodiment includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, the silicon-based active substance includes silicon element and lithium silicate, and the silicon element includes nano-silicon grains; the negative electrode material is measured by XRD ray diffraction method, and the X-ray diffraction spectrum of the negative electrode material is calculated to obtain the relationship between A, B, and C in the negative electrode material: (A+B) / C=5.1, (A+C) / B=2.0, (B+C) / A=10.3, the relationship between ρ1, ρ2, σ1, and σ2 satisfies: (σ2-σ1) / (ρ2-ρ1)=0.33, and the relationship between shear forces in the rheological curve satisfies 2τ1>(τ2-τ0).

[0137] The negative electrode material prepared in this embodiment can be stably stored for more than 72 hours after being prepared into negative electrode slurry.

[0138] Example 3

[0139] The negative electrode material was prepared in a method substantially the same as that in Example 1, except that:

[0140] (2) A mixture of 1000 g of surface-modified silicon monoxide (SiO) and 150 g of metallic lithium is placed in a high-speed disperser, argon gas is introduced, the temperature is raised to 80° C., and the mixture is dispersed at 2000 rpm for 1 h for mixing. The mixture is cooled to room temperature and then loaded into a crucible. The crucible is placed in a box furnace for pre-lithiation treatment at 500° C. for 4 h, and the temperature is lowered to 25° C. to obtain a silicon-based active substance. Then, 2% wt of amorphous carbon is coated on the surface of the silicon-based active substance by a liquid phase coating method to obtain a precursor.

[0141] The remaining operations are the same as those in Example 1.

[0142] The negative electrode material prepared in this embodiment includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, the silicon-based active substance includes silicon element and lithium silicate, and the silicon element includes nano-silicon grains; the negative electrode material is measured by XRD ray diffraction method, and the X-ray diffraction spectrum of the negative electrode material is calculated to obtain the relationship between A, B, and C in the negative electrode material: (A+B) / C=4.1, (A+C) / B=2.2, (B+C) / A=8.8, the relationship between ρ1, ρ2, σ1, and σ2 satisfies: (σ2-σ1) / (ρ2-ρ1)=0.46, and the relationship between shear forces in the rheological curve satisfies 2τ1>(τ2-τ0).

[0143] The negative electrode material prepared in this embodiment can be stably stored for more than 72 hours after being prepared into negative electrode slurry.

[0144] Example 4

[0145] (1) Silicon oxide (SiO 1.5 ) was placed in a mixed acid solution of nitric acid and hydrochloric acid with a concentration of 1 mol / L, stirred and dispersed at 50°C for 4 hours, then filtered and washed with pure water, and the obtained product was dried at 80°C to obtain silicon oxide (SiO 1.5 ).

[0146] (2) 1000 g of surface-modified silicon oxide (SiO 1.5 ) and 100g of alkyl lithium are placed in a high-speed disperser, argon is introduced, the temperature is raised to 80°C, and the mixture is dispersed at 2000 rpm for 1 hour for mixing treatment. The mixture is cooled to room temperature and then loaded into a crucible. The crucible is placed in a box furnace for pre-lithiation treatment at 500°C for 4 hours, and the temperature is lowered to 25°C to obtain a silicon-based active substance. Then, 2% wt of amorphous carbon is coated on the surface of the silicon-based active substance by a liquid phase coating method to obtain a precursor.

[0147] (3) The precursor is placed in Al(OH)3 and purified at 40°C for 2h. The residual alkali solution on the surface of the precursor is removed by filtration and washing. Then, 2%wt of amorphous carbon is coated on the surface of the precursor by a liquid phase coating method to obtain a negative electrode material.

[0148] The negative electrode material prepared in this embodiment includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, the silicon-based active substance includes silicon element and lithium silicate, and the silicon element includes nano-silicon grains; the negative electrode material is measured by XRD ray diffraction method, and the X-ray diffraction spectrum of the negative electrode material is calculated to obtain the relationship between A, B, and C in the negative electrode material: (A+B) / C=2.5, (A+C) / B=1.8, (B+C) / A=1.2, the relationship between ρ1, ρ2, σ1, and σ2 satisfies: (σ2-σ1) / (ρ2-ρ1)=0.52; the relationship between shear forces in the rheological curve satisfies 2τ1>(τ2-τ0).

[0149] The negative electrode material prepared in this embodiment can be stably stored for more than 72 hours after being prepared into negative electrode slurry.

[0150] Example 5

[0151] The negative electrode material was prepared in a method substantially the same as that in Example 1, except that:

[0152] (1) Silicon monoxide (SiO) is placed in a mixed acid solution of nitric acid and hydrochloric acid with a concentration of 2 mol / L, stirred and dispersed at 50° C. for 4 h, then filtered and washed with pure water, and the obtained product is dried at 80° C. to obtain silicon monoxide (SiO) after surface modification.

[0153] The remaining operations are the same as those in Example 1.

[0154] The negative electrode material prepared in this embodiment includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, the silicon-based active substance includes silicon element and lithium silicate, and the silicon element includes nano-silicon grains; the negative electrode material is measured by XRD ray diffraction method, and the X-ray diffraction spectrum of the negative electrode material is calculated to obtain the relationship between A, B, and C in the negative electrode material: (A+B) / C=2.8, (A+C) / B=1.5, (B+C) / A=1.9, the relationship between ρ1, ρ2, σ1, and σ2 satisfies: (σ2-σ1) / (ρ2-ρ1)=0.61, and the relationship between shear forces in the rheological curve satisfies 2τ1>(τ2-τ0).

[0155] The negative electrode material prepared in this embodiment can be stably stored for more than 72 hours after being prepared into negative electrode slurry.

[0156] Example 6

[0157] The negative electrode material was prepared in a method substantially the same as that in Example 1, except that:

[0158] (2) A mixture of 1000 g of surface-modified silicon monoxide (SiO) and 200 g of lithium hydride was placed in a high-speed disperser, argon was introduced, the temperature was raised to 80° C., and the mixture was dispersed at 2000 rpm for 1 h for mixing. The mixture was cooled to room temperature and then placed in a crucible. The crucible was placed in a box furnace for pre-lithiation treatment at 300° C. for 5 h, and the temperature was lowered to 25° C. to obtain a silicon-based active material. Then, 2% wt of amorphous carbon was coated on the surface of the silicon-based active material by a liquid phase coating method to obtain a precursor. The remaining operations were the same as those in Example 1.

[0159] The negative electrode material prepared in this embodiment includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, the silicon-based active substance includes silicon element and lithium silicate, and the silicon element includes nano-silicon grains; the negative electrode material is measured by XRD ray diffraction method, and the X-ray diffraction spectrum of the negative electrode material is calculated to obtain the relationship between A, B, and C in the negative electrode material: (A+B) / C=10, (A+C) / B=1.0, (B+C) / A=30, the relationship between ρ1, ρ2, σ1, and σ2 satisfies: (σ2-σ1) / (ρ2-ρ1)=0.46, and the relationship between shear forces in the rheological curve satisfies 2τ1>(τ2-τ0).

[0160] The negative electrode material prepared in this embodiment can be stably stored for more than 72 hours after being prepared into negative electrode slurry.

[0161] Example 7

[0162] The negative electrode material was prepared in a method substantially the same as that in Example 1, except that:

[0163] (2) A mixture of 1000 g of surface-modified silicon monoxide (SiO) and 200 g of lithium hydride is placed in a high-speed disperser, argon gas is introduced, the temperature is raised to 80° C., and the mixture is dispersed at 2000 rpm for 1 h for mixing. The mixture is cooled to room temperature and then loaded into a crucible. The crucible is placed in a box furnace for pre-lithiation treatment at 800° C. for 4 h, and the temperature is lowered to 25° C. to obtain a silicon-based active substance. Then, 2% wt of amorphous carbon is coated on the surface of the silicon-based active substance by a liquid phase coating method to obtain a precursor.

[0164] The remaining operations are the same as those in Example 1.

[0165] The negative electrode material prepared in this embodiment includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, the silicon-based active substance includes silicon element and lithium silicate, and the silicon element includes nano-silicon grains; the negative electrode material is measured by XRD ray diffraction method, and the X-ray diffraction spectrum of the negative electrode material is calculated to obtain the relationship between A, B, and C in the negative electrode material: (A+B) / C=1.3, (A+C) / B=5, (B+C) / A=29.3, the relationship between ρ1, ρ2, σ1, and σ2 satisfies: (σ2-σ1) / (ρ2-ρ1)=0.5, and the relationship between shear forces in the rheological curve satisfies 2τ1>(τ2-τ0).

[0166] The negative electrode material prepared in this embodiment can be stably stored for more than 72 hours after being prepared into negative electrode slurry.

[0167] Comparative Example 1

[0168] The difference from Example 1 is that:

[0169] In this embodiment, except that in step (2), the crucible is placed in a box furnace for pre-lithiation treatment at 200° C. for 5 h, other operating conditions and raw materials are the same as those in Example 1.

[0170] The negative electrode material prepared in this comparative example includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, wherein the silicon-based active substance includes silicon element and lithium silicate; the negative electrode material is measured by XRD ray diffraction method, and the X-ray diffraction spectrum of the negative electrode material is calculated to obtain the relationship between A, B, and C in the negative electrode material: (A+B) / C=8, (A+C) / B=13, (B+C) / A=40, the relationship between ρ1, ρ2, σ1, and σ2 satisfies: (σ2-σ1) / (ρ2-ρ1)=0.9, and the relationship between shear forces in the rheological curve satisfies 2τ1>(τ2-τ0).

[0171] The negative electrode material prepared in this comparative example cannot be stably stored after being prepared into negative electrode slurry.

[0172] Comparative Example 2

[0173] The difference from Example 1 is that:

[0174] In this embodiment, except that in step (2), the crucible is placed in a box furnace for pre-lithiation treatment at 900° C. for 2 h, other operating conditions and raw materials are the same as those in Example 1.

[0175] The negative electrode material prepared in this comparative example includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, wherein the silicon-based active substance includes silicon element and lithium silicate; the negative electrode material is measured by XRD ray diffraction method, and the X-ray diffraction spectrum of the negative electrode material is calculated to obtain the relationship between A, B, and C in the negative electrode material: (A+B) / C=1.8, (A+C) / B=18, (B+C) / A=30, the relationship between ρ1, ρ2, σ1, and σ2 satisfies: (σ2-σ1) / (ρ2-ρ1)=0.96, and the relationship between shear forces in the rheological curve satisfies 2τ1<(τ2-τ0).

[0176] The negative electrode material prepared in this comparative example cannot be stably stored after being prepared into negative electrode slurry.

[0177] Comparative Example 3

[0178] The difference from Example 1 is that:

[0179] In this comparative example, the process of step (1) of Example 1 is not performed, and other operating conditions and raw materials are the same as those of Example 1.

[0180] The negative electrode material prepared in this comparative example includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, wherein the silicon-based active substance includes silicon element and lithium silicate; the negative electrode material is measured by XRD ray diffraction method, and the X-ray diffraction spectrum of the negative electrode material is calculated to obtain the relationship between A, B, and C in the negative electrode material: (A+B) / C=2.1, (A+C) / B=6.2, (B+C) / A=6.9, the relationship between ρ1, ρ2, σ1, and σ2 satisfies: (σ2-σ1) / (ρ2-ρ1)=0.72, and the relationship between shear forces in the rheological curve satisfies 2τ1<(τ2-τ0).

[0181] The negative electrode material prepared in this comparative example cannot be stably stored after being prepared into negative electrode slurry.

[0182] Comparative Example 4

[0183] The difference from Example 1 is that:

[0184] This comparative example does not carry out the process of step (3) of Example 1, and other operating conditions and raw materials are the same as those of Example 1.

[0185] The negative electrode material prepared in this comparative example includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, wherein the silicon-based active substance includes silicon element and lithium silicate; the negative electrode material is measured by XRD ray diffraction method, and the X-ray diffraction spectrum of the negative electrode material is used to calculate that the relationship between A, B, and C in the negative electrode material satisfies: (A+B) / C=1.8, (A+C) / B=7.0, (B+C) / A=19, the relationship between ρ1, ρ2, σ1, and σ2 satisfies: (σ2-σ1) / (ρ2-ρ1)=0.96, and the relationship between shear forces in the rheological curve satisfies 2τ1<(τ2-τ0).

[0186] The negative electrode material prepared in this comparative example cannot be stably stored after being prepared into negative electrode slurry.

[0187] Test method:

[0188] (1) XRD test method of negative electrode materials:

[0189] The XRD spectrum of the material was tested according to the equipment and methods used in the operating instructions of BTRTC / ZY / 02-008 "X-ray Diffractometer Test Operating Instructions". Equipment test parameters: divergence slit 1.0°, anti-scattering slit 2.0°, receiving slit 9.6°, voltage range 40KV, current 40mA, scanning range 10-90°, scanning step (scan step) 0.01313, scanning mode is continuous, each step scanning time 10.2s, calculated wavelength

[0190] (2) Test method for powder conductivity and powder density of negative electrode materials:

[0191] The powder conductivity of the material was tested according to the equipment and methods used in the operating instructions of BTRTC / ZY / 02-093 "Powder Conductivity Test Operating Instructions" of BTR Company. The test equipment comes from Mitsubishi Chemical of Japan. The test parameters are: the initial resistance magnitude can be selected as -3, the voltage limit can be selected as 10V, and the sample quality must ensure that the sample thickness is 3 to 5mm under a pressure of 20KN. The pressures were set to 4, 8, 12, 16, and 20KN, the Electrode radius was 0.7mm, and the Sample radius was 10mm, and the powder density and powder conductivity were measured.

[0192] (3) Testing method of rheological curve of negative electrode slurry:

[0193] Active material, carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber are mixed in a mass ratio of 95.3:1.3:1.5:1.9 to form a negative electrode slurry with a solid content of 50%, wherein the active material includes negative electrode material and graphite in a mass ratio of 9:1; the rheological properties of the negative electrode slurry are tested using a German Haake rotational rheometer to obtain the rheological curve of the negative electrode slurry.

[0194] (4) 50-cycle performance test with power off

[0195] According to the equipment and methods used in the operating instructions of BTRTC / ZY / 01-020 "Button Cell Method Operating Instructions" of BTR Company: button cells are assembled. Among them, metal lithium sheets are used for the counter electrode, and the separator is a PP-PE-PP composite film with a diameter of 19.2mm; the electrolyte component ratio is EC / EMC / DMC=1 / 1 / 1, and the lithium salt (LiPF6) concentration is 1.05mol / L. Using the button cell charging and discharging equipment, in the first week, 0.1C discharge to 0.01V, 0.01C arithmetic decrease discharge to 0.01V, 0.01C discharge to 0.005V, 0.1C charge to 1.5V; in the second week, 0.2C discharge to 0.01V, 0.02C arithmetic decrease discharge to 0.01V, 0.02C discharge to 0.005V, 0.2C charge to 1.5V; in the third week, 0.5C discharge to 0.01V, 0. 0.5C discharge in equal steps to 0.01V, 0.05C discharge to 0.005V, 0.5C charge to 1.5V; from the 4th to the 50th week, 1C discharge to 0.01V, 0.1C discharge in equal steps to 0.01V, 0.1C discharge to 0.005V, 1C charge to 1.5V; in the 51st week, 0.1C discharge to 0.01V, 0.01C discharge in equal steps to 0.01V, 0.01C discharge to 0.005V, 0.01C charge to 1.5V.

[0196] (5) Negative electrode slurry storage stability assessment method:

[0197] Active materials, carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber were mixed in a mass ratio of 95.3:1.3:1.5:1.9 to form a negative electrode slurry with a solid content of 50%, wherein the active materials included negative electrode materials and graphite in a mass ratio of 9:1, and then the negative electrode slurry was allowed to stand at 25°C to observe changes in viscosity, fluidity, solid content, fineness, coating conditions, etc. during the standing process of the slurry. If the viscosity increases or decreases, it means that the slurry may have particle aggregation or dispersion, which is not conducive to the stability of the slurry; if obvious stratification and fluid thickening occur, it means that the slurry has reduced dispersion, poor fluidity, and reduced stability; if the solid content changes significantly, particles will aggregate or precipitate in the slurry, affecting its stability; if larger particles aggregate or the fineness of the particles changes significantly, the stability of the slurry will decrease; the slurry is coated on the substrate, and the uniformity and adhesion of the coating are observed. If the coating is uneven, falls off or cracks, it means that the slurry has poor stability.

[0198] (6) Test method for specific capacity:

[0199] Use button battery charging and discharging equipment, 0.1C constant current charging to 10mV, then 0.02C constant current charging to 5mV, and 0.1C constant current discharging to 1.5V cutoff.

[0200] The above test results are detailed in Table 1.

[0201] Table 1 Test results of embodiments and ratios

[0202]

[0203]

[0204] From the above embodiments and comparative examples, it can be known that embodiments 1 to 7 can improve the lithiation uniformity of the negative electrode material and the processing performance of the negative electrode material by controlling the balance relationship between the three components of Li2SiO3, Li2Si2O5 and silicon in the negative electrode material, thereby improving the storage stability of the negative electrode slurry prepared from the negative electrode material; by controlling the balance relationship between the three components of Li2SiO3, Li2Si2O5 and silicon in the negative electrode material, the content of Li2Si2O5 in the negative electrode material can be increased, the destructive effect of lithium silicate on the binder can be reduced, the stability of the electrode sheet can be improved, the cycle performance of the negative electrode material can be improved, and the cycle life can be extended.

[0205] Compared with Example 1, the temperature of the pre-lithiation treatment of the negative electrode material in Comparative Example 1 is too low. During the pre-lithiation process, the lithium source cannot react completely with silicon monoxide, and the prepared negative electrode material has a high oxygen content, resulting in a low initial efficiency of the negative electrode material.

[0206] Compared with Example 1, the temperature of the pre-lithiation treatment of the negative electrode material in Comparative Example 2 is too high. During the pre-lithiation process, the lithium source and silicon monoxide react violently, and lithium silicate is generated at a fast rate and in large quantities. On the one hand, it catalyzes the growth of silicon grains in the negative electrode material, resulting in degradation of the material's cycle performance; on the other hand, it reduces the storage stability of the negative electrode slurry made of the negative electrode material, making it impossible to store the slurry stably for a long time.

[0207] Compared with Example 1, the negative electrode material of Comparative Example 3 does not perform surface modification on silicon monoxide, the reaction sites in the pre-lithium process are reduced, the pre-lithium reaction is uneven, the growth sites of lithium silicate are reduced, and the lithium silicate inside the negative electrode material particles is unevenly distributed, which is not conducive to the regulation of the crystal phase type and content of lithium silicate, resulting in an imbalance in the relative relationship between the three components of Li2SiO3, Li2Si2O5 and silicon element in the negative electrode material, thereby reducing the storage performance of the negative electrode slurry made of the negative electrode material, and the negative electrode slurry cannot be stored stably for a long time. The slurry is prone to sedimentation, stratification, and gas production during storage, resulting in uneven distribution of active substances in the coated electrode sheet, and the lithium silicate in the negative electrode material has a large destructive effect on the binder, which reduces the structural stability of the electrode sheet and causes a decrease in the cycle performance of the negative electrode material.

[0208] Compared with Example 1, the negative electrode material of Comparative Example 4 does not perform a second surface treatment on the precursor. On the one hand, the interface stability of the negative electrode material is poor, the performance stability of the formed SEI film is reduced, and the corrosion risk of the negative electrode material in the electrolyte is increased. On the other hand, the adhesion strength of the binder to the negative electrode material is weakened, the peel strength of the electrode piece is reduced, the electrode piece is easy to rebound, the stability of the conductive network of the electrode piece is reduced, and the cycle performance of the negative electrode material is reduced.

Claims

1. A negative electrode material, characterized in that: The negative electrode material includes a silicon-based active material and a carbon material located on at least a portion of the surface of the silicon-based active material, wherein the silicon-based active material includes silicon and lithium silicate; Determined by XRD ray diffraction method, in the X-ray diffraction spectrum of the negative electrode material, the peak intensity of the strongest diffraction peak of the negative electrode material in the range of 2θ of 18° to 20° is A1, the peak intensity of the strongest diffraction peak in the range of 2θ of 26° to 27.9° is A2, and the peak intensity of the strongest diffraction peak at 2θ of 32° to 34° is A3, and A1+A2+A3=A; The peak intensity of the strongest diffraction peak of the negative electrode material in the range of 2θ of 16° to 17° is B1, the peak intensity of the strongest diffraction peak in the range of 2θ of 22° to 25.9° is B2, and the peak intensity of the strongest diffraction peak in the range of 2θ of 36° to 38° is B3, B1+B2+B3=B; The peak intensity of the strongest diffraction peak of the negative electrode material in the range of 28° to 30° at 2θ is C1, the peak intensity of the strongest diffraction peak in the range of 46° to 48° at 2θ is C2, and the peak intensity of the strongest diffraction peak in the range of 56° to 58° at 2θ is C3, C1+C2+C3=C; And the relationship between A, B, and C satisfies the following conditions at the same time: 0<(A+B) / C≤10, 0<(A+C) / B≤5.

2. The negative electrode material according to claim 1, characterized in that The negative electrode material is tested using a powder resistivity tester, and the powder conductivity of the negative electrode material at a powder density of ρ1 is measured to be σ1, and the powder conductivity of the negative electrode material at a powder density of ρ2 is measured to be σ2, and the following relationship is satisfied: (σ2-σ1) / (ρ2-ρ1)≤0.

8.

3. The negative electrode material according to claim 1, characterized in that It satisfies at least one of the following characteristics (1) to (11): (1) The silicon-based active material also includes a silicon-oxygen composite; (2) The molar ratio of oxygen atoms to silicon atoms in the negative electrode material is 0.5 to 2; (3) The silicon single substance includes nano-silicon grains, and the particle size of the nano-silicon grains is 0 nm to 20 nm, and does not include 0 nm; (4) The carbon material includes at least one of amorphous carbon, graphene, graphite, carbon nanotubes and carbon fibers; (5) The lithium silicate includes at least one of Li2SiO3, Li2Si2O5 and Li4SiO4; (6) The mass content of the carbon material in the negative electrode material is less than or equal to 10%; (7) The specific surface area of ​​the negative electrode material is less than or equal to 10 m 2 / g; (8) The relationship between A, B, and C also satisfies: 1≤(B+C) / A≤30; (9) The mass content of silicon in the negative electrode material is 20% to 70%; (10) The mass content of lithium silicate in the negative electrode material is 30% to 75%; (11) The pH value of the negative electrode material is 7.2 to 11.

0.

4. The negative electrode material according to any one of claims 1 to 3, characterized in that Active material, carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber are mixed in a mass ratio of 95.3:1.3:1.5:1.9 to form a negative electrode slurry with a solid content of 50%, wherein the active material includes the negative electrode material and graphite in a mass ratio of 9:1; the rheological properties of the negative electrode slurry are tested using a German Haake rotational rheometer to obtain a rheological curve of the negative electrode slurry; in the rheological curve, when the shear rate is 0S -1 、150S -1 、300S -1 When , the corresponding shear stresses in the rheological curve are τ0, τ1, τ2, and the relationship between the shear stresses satisfies: 2τ1>(τ2-τ0).

5. A method for preparing a negative electrode material, characterized in that: The following steps are involved: Silicon oxide SiO x Place in an acid solution for the first surface modification treatment, wherein 0<x<2; The silicon oxide SiO x The mixture with the reducing lithium-containing compound is subjected to a pre-lithiation treatment and a carbon coating treatment at 300° C. to 800° C. to obtain a precursor, wherein 0<x<2; The precursor is subjected to a second surface modification treatment to obtain a negative electrode material, wherein the negative electrode material includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance, and the silicon-based active substance includes silicon and lithium silicate.

6. The preparation method according to claim 5, characterized in that: It satisfies at least one of the following characteristics (1) to (6): (1) The acid solution includes at least one of hydrofluoric acid, nitric acid, fluorosulfonic acid, fluoroantimonysulfonic acid, hydrochloric acid, hydrobromic acid, and hydroiodic acid; (2) The concentration of the acid solution is ≤ 2 mol / L; (3) The temperature of the first surface modification treatment is 30°C to 100°C; (4) The first surface modification treatment lasts for 2 to 8 hours; (5) The preparation method further comprises treating the silicon oxide SiO x Carry out solid-liquid separation, washing and drying; (6) The preparation method further comprises treating the silicon oxide SiO x Solid-liquid separation, washing and drying are performed, and the drying temperature is 50°C to 180°C.

7. The preparation method according to claim 5, characterized in that: It satisfies at least one of the following characteristics (1) to (9): (1) The silicon oxide is silicon monoxide; (2) the reducing lithium-containing compound comprises at least one of lithium hydride, alkyl lithium, metallic lithium, lithium aluminum hydride, lithium amide, lithium borohydride and lithium silicon alloy; (3) The mass ratio of the silicon oxide after the first surface modification treatment to the reducing lithium-containing compound is 1:(0.03-0.2); (4) The pre-lithiation treatment is carried out in a protective atmosphere; (5) The pre-lithiation treatment is performed in a protective atmosphere, wherein the protective atmosphere comprises at least one of nitrogen, helium, neon, argon, krypton and xenon; (6) The pre-lithiation treatment time is 3h to 9h; (7) The carbon coating process includes at least one of a liquid phase coating method, a gas phase coating method and a solid phase coating method; (8) The carbon-coated coating material includes at least one of amorphous carbon, graphene, graphite, carbon nanotubes and carbon fibers; (9) The lithium silicate includes at least one of Li2SiO3, Li2Si2O5, and Li4SiO4.

8. The preparation method according to claim 5, characterized in that: After the first surface modification treatment, the silicon oxide SiO x Before the mixture with the reducing lithium-containing compound is subjected to a pre-lithiation treatment at 300° C. to 800° C., the method further comprises treating the silicon oxide SiO x The mixture is mixed with a reducing lithium-containing compound, which satisfies at least one of the following characteristics (1) to (3): (1) The temperature of the mixing treatment is 60° C. to 320° C.; (2) The mixing treatment time is 0.5h to 10h; (3) The equipment required for the mixing process includes at least one of an equipment with a dispersing function and an equipment with a shearing force effect.

9. The preparation method according to claim 5, characterized in that: It satisfies at least one of the following characteristics (1) to (4): (1) The second surface treatment includes at least one of purification treatment, coating treatment, heat treatment, oxidation treatment, and etching treatment; (2) The temperature of the second surface treatment is 50° C. to 900° C.; (3) The second surface treatment time is 0.5h to 10h; (4) The second surface treatment includes placing the precursor in an aluminum hydroxide solution for purification.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode material according to any one of claims 1 to 4 or the negative electrode material prepared according to the method for preparing the negative electrode material according to any one of claims 5 to 9.

Citation Information

Cited By

  • Negative electrode material, negative electrode slurry, and lithium ion battery

    EP4601036A1

  • Negative electrode material, negative electrode slurry, and lithium ion battery

    WO2025060430A1